Histological Response of Broiler’s Immune Related Organs to Feeding Different Direct Fed Microbials - El-Azeem, Nafisa A. Abd; El-Daly, Eman F.; Hassan, H.M.A.; Youssef, Amani W.; Mohamed , M.A. (International Journal of Poultry Science, 2015)
An experiment was conducted to study the effect of feeding different commercial preparations of direct-fed microbials (DFM) used as growth promoters on weight and histology of immune related organs (bursa, thymus and spleen) in broilers. Two hundred unsexed 10 days old Cobb broiler chicks were individually weighed and divided into 4 groups (5 replicates of 10 chicks, each) and fed 4 different experimental diets. A mixture of Enterococcus faecium (Protexin®, DFM1), a mixture of Bacillus subtilis (Clostat®, DFM2) and Saccharomyces cerevisiae yeast cells with its fermentation metabolites (Diamond®, DFM3) were supplemented to broiler diets and compared with the basal diet which served as control. Bursa, thymus and spleen were taken from birds at 36 days of age. The results showed significant (P